2023
DOI: 10.1002/casp.2760
|View full text |Cite
|
Sign up to set email alerts
|

‘Take Back the Land’: Analysis of the influence of environmental concern, cultural tightness and moral disengagement on pro‐environmental behaviour intentions

Daniela Di Santo,
Dario Di Santo,
Antonio Pierro

Abstract: Our study found that individuals' environmental concerns are positively associated with their pro‐environmental behavioural intentions through increased desired cultural tightness and reduced moral disengagement. Based on past research on (a) the positive association between personal concerns for ecological threats and desire for strong rules and punishment for violation (i.e., cultural tightness) and (b) the negative impact of moral disengagement on pro‐environmental behavioural intention, we proposed that pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Although this model has not yet been tested, the individual pathways are supported by previous research: for instance, Mula and Pierro (2022) found that the prevention focus and desired tightness are related; Di Santo et al (2024) that desired tightness and moral disengagement are related; Fehr et al (2019) that moral disengagement and reactions to norm violations are related. The hypothesized model was support and results were consistent with those uncovered by previous research.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Although this model has not yet been tested, the individual pathways are supported by previous research: for instance, Mula and Pierro (2022) found that the prevention focus and desired tightness are related; Di Santo et al (2024) that desired tightness and moral disengagement are related; Fehr et al (2019) that moral disengagement and reactions to norm violations are related. The hypothesized model was support and results were consistent with those uncovered by previous research.…”
Section: Discussionmentioning
confidence: 57%
“…However, an interesting feature of tightness is that individuals can desire a particular amount of tightness or looseness independent of whatever level of tightness or looseness that exists in their nation, region, etc. Individual-level desire for tightness or looseness, independent of the cultural level, has been found to predict negative reactions to organizational norm violations ( Mula and Pierro, 2022 ), negative reactions to COVID norm violations ( Baldner et al, 2022 ), and lower levels of moral disengagement ( Di Santo et al, 2024 ). The rationale underlying these findings is that a desire for rigid norms is contrary to both committing norm violations as well as justifications for such violations (e.g., moral disengagement).…”
Section: Introductionmentioning
confidence: 99%